(untitled) (University of Khartoum Journal of Agricultural Sciences, 2023)
This study was conducted to evaluate the quality of pasteurizedmilk which is produced in three dairy plants in Khartoum State during astorage period of 10 days. Forty- five samples of pasteurized milk wererandomly collected from three different plants (A, B and C) to determinethe chemical composition fat, protein, solids-non-fat (SNF), lactose,acidity and density and microbiological quality total viable bacteria(TVB), coliform bacteria and psychroptrophic bacteria counts at 1, 4, 6,8 and 10-day intervals. The results showed that fat, protein, lactose,density and acidity were significantly affected by the source of milk,while SNF was not affected. Coliform and psychrotrophic bacteria countswere significantly affected by the plant from which the milk samples werecollected, whereas TVB was not affected. During the storage period, fatcontent decreased, while protein, density and acidity increased, and SNFand lactose contents did not significantly change. Coliform bacteria countdecreased, while psychrotrophic bacteria count increased, and nosignificant change was obtained for total viable bacteria (TVBC) count.